Iraq : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2015)
This Selected Issues paper focuses on the Iraqi oil sector and analyzes the developments and prospects after the twin shock. The Iraqi economy was affected by the two major challenges during 2014-ISIS insurgency and the fall in global oil prices. Iraq's oil sector has performed well despite the security challenges that emerged after the onset of the ISIS insurgency in June 2014. On average, Iraq earned USD 97 per barrel on oil exported in 2014. Asia remained the leading destination of the Iraqi oil exports during 2013-14, and its share increased from 50 percent in 2012 to 65 percent in 2014.